2007
DOI: 10.1002/bip.20663
|View full text |Cite
|
Sign up to set email alerts
|

Switch‐peptides as folding precursors in self‐assembling peptides and amyloid fibrillogenesis

Abstract: The study of conformational transitions of peptides has obtained considerable attention recently because of their importance as a molecular key event in a variety of degenerative diseases. However, the study of peptide selfassembly into β‐sheets and amyloid β (Aβ) fibrils is strongly hampered by their difficult synthetic access and low solubility. We have recently developed a new concept termed “switch‐peptides” that allows the controlled onset of polypeptide folding and misfolding at physiologic conditions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 57 publications
0
38
0
1
Order By: Relevance
“…To overcome this limitation, we utilized the residue serine118, which is located in the center of the active sequence, to design a depsipeptic derivative of cgg-Poro2 (Figure 2). The displacement of the peptidic chain from the a amino group to the hydroxyl of a serine side chain was proposed simultaneously by the groups of Kiso 45 and Mutter 46 to handle the synthesis of aggregating sequences. The O-acylated derivative of the peptide may undergo an O-N acyl shift in neutral or basic conditions to yield the desired linear peptide sequence.…”
Section: Scaled-up Production Of the Peptidesmentioning
confidence: 99%
“…To overcome this limitation, we utilized the residue serine118, which is located in the center of the active sequence, to design a depsipeptic derivative of cgg-Poro2 (Figure 2). The displacement of the peptidic chain from the a amino group to the hydroxyl of a serine side chain was proposed simultaneously by the groups of Kiso 45 and Mutter 46 to handle the synthesis of aggregating sequences. The O-acylated derivative of the peptide may undergo an O-N acyl shift in neutral or basic conditions to yield the desired linear peptide sequence.…”
Section: Scaled-up Production Of the Peptidesmentioning
confidence: 99%
“…An important aspect of our synthesis is the use of the one-pot approach to include the desulfurization step; this reduces the number of purification steps and significantly increases the synthesis yield. Having these synthesis tools in hand, we plan to study the effect of post-translational modifications [54][55][56] on the function and structure of the Rev protein, along with introducing chemical switches [57,58] to control Rev folding and self-assembly, to better understand these processes on the function of Rev protein. [4,53,59] …”
Section: Expression Of Hiv-1 Revmentioning
confidence: 99%
“…Previously, we [5][6][7][8] and others [9][10][11][12] have shown that various steps along the amyloid formation pathway, including peptide/ protein misfolding, self-assembly, and amyloid formation and disassembly, can be triggered in a highly controllable manner through the incorporation of molecular switches into the amyloid-forming polypeptides, based on in situ intramolecular O! N acyl migration.…”
Section: Introductionmentioning
confidence: 99%
“…N acyl migration. [5][6][7][8][9][10][11][12][13][14][15][16] However, because of the special synthetic and purification skills required to prepare the full-length Ab switch-peptides, such peptides are not suitable for use in highthroughput screening assays. Therefore, the development of reliable model systems that are readily accessible and adaptable to automated HTS is of particular interest to understanding the mechanism of amyloid formation and facilitating the discovery of aggregation inhibitors of Ab and other amyloid-forming proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation